UTILIZATION OF ICT TO IMPROVE MATHEMATICAL LITERACY SKILLS - Fauzi, Ahmad Lutfi; Nurlaelah, Elah; Dasari, Dadan; Supriyadi, Edi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
ICT is one of the learning media that supports the process of teaching and learning activities. Mathematical literacy ability is one of the abilities to be able to interpret a problem in the text. The purpose of this study was to determine the use of ICT on mathematical literacy skills. The methodology used is a mixed-method, the object of research is a class X student in one of the senior high schools in Bandung. The instruments in this study were student worksheets, initial pretest, postest, questionnaires and interviews. Analysis of the data used. The results of the study obtained an increase, and included in the low category, but with ICT students can increase student creativity independently.